(3cJGH GdeYWjGJs - (3GbdjOSs
(3ChdgG (B:s
(3GdeYdheI GdYOO gi GdJi jecf Cf JLO eSGhjI dgG s
(3BNQgG (B:s
(3hPdc eG CQOfGg NJe cJGH GdeYWjGJ hGdMeO ddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1460s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdQjGVjGJs